Peningkatkan Partisipasi Aktif Siswa melalui Metode Role Play pada Pembelajaran Bahasa Indonesia Kelas III SD - Devina Abidah Ardelia; Hamidatin Na'imah; Anzala Huwaidah; Tyasmiarni Tyasmiarni Citrawati (Yayasan Citra Dharma Cindekia, 2026)
Low student participation in Indonesian language learning, particularly in learning the use of capital letters, was identified among third-grade students at UPTD SDN 3 Socah. To address this issue, this study investigated the implementation of the role play method to improve students' active participation and learning outcomes. The study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The participants were 20 third-grade students. Data were collected through classroom observations, achievement tests, and documentation, and were analyzed using descriptive qualitative and quantitative techniques. The findings revealed that the implementation of the role play method improved both student participation and learning outcomes. Student participation increased from 40% in the first cycle to 80% in the second cycle. In addition, the number of students who achieved mastery learning increased from 9 students (45%) in Cycle I to 15 students (75%) in Cycle II. Students demonstrated greater confidence in answering questions, expressing ideas, participating in discussions, and completing assigned tasks. The learning process also became more interactive and engaging. These findings indicate that the role play method is effective in enhancing students' active participation and learning outcomes in Indonesian language learning, particularly in the topic of capital letter usage at the primary school level.